Proposed syllabus in algebra in Mathematics 10 for first year comprehensive high school in Thailand - Thaijaidee, Yuenyong 1945- (1974)
This proposed syllabus is intended to guide the teacher of Mathematics 10 in Mathayom Suksa 1 for first year comprehensive high school in Thailand. There are 8 chapters in this syllabus with topics on: sets, numbers and symbols for numbers, counting numbers, integers, rational numbers, ratio and percent, measurement, and areas and volumes.
Thesis (M.A.T.Mathematics)--University of the Philippines
Keywords: Mathematics -- Study and teaching (Secondary) -- Thailand; Algebra -- Outlines, syllabi etc; Mathematics -- Outlines, syllabi, etc